Quantification of climate change impact on hydrological extremes in the Upper Tekeze basin in the future with two ensemble strategies - Reda, Kidane Welde; Liu, Xingcai; Tang, Qiuhong; Gaffney, Paul PJ; Xu, Ximeng (Theoretical and applied climatology, 2025)
Ensemble means of General Circulation Models (GCMs) were generally used to produce future projections of hydrological extremes in combination with hydrological models. However, this method may be subject to considerable uncertainties due to the discrepancies of GCMs in reproducing regional climate changes. In this study, we used two multi-model ensemble strategies (simple-averaged and flow-based weighted) that integrates projections of GCMs with a hydrological model, Soil and Water Assessment Tool (SWAT). The results showed that, compared to the reference period (1981–2022), the long-term daily temperatures were projected to increase while no significant trend was found in precipitation in near (2040s: 2023–2061) and distant (2080s: 2062–2100) future using the two ensemble strategies. The streamflow was predicted to decrease from May to October while negligible changes were projected from December to March at three stations of the UTB during the future periods. The flow-weighted ensemble strategy outperformed the averaged in reproducing hydrological regimes and thus may produce more robust projections of hydrological changes. However, the two ensemble strategies underestimated the frequency and magnitude of flow extremes. Therefore, the range in the magnitude of extreme flow events that together defined by individual GCMs can also provide critical information on future water resources planning. A distinct level of heterogeneity in changes of hydrological components are projected across the sub-watersheds. An increase in evapotranspiration and decrease in surface runoff and soil water are observed. Overall, our findings suggest that future water resources planning and development exercises need to fully consider the effects of climate change.